Remote sensing analysis of post-typhoon damage and recovery, and assessment of diversity and carbon stock of a mangrove forest in San Policarpo, Eastern Samar - Acol, Raisa Ashley L. (2024)
In this study, a time series analysis of the normalized difference vegetation index (NDVI) and the mangrove vegetation index (MVI) was conducted to determine the extent of mangrove damages and recovery in Brgy. Japunan, San Policarpo, Eastern Samar after Typhoon Vongfong. Intensified field sampling was also carried out at the study site to determine the diversity and carbon sequestration potential of the mangrove stand. Based on the MVI-generated maps, the mangrove cover loss between April 2020 and August 2020 was approximately 41.40 hectares, or 55.17%. During the same period, the mean NDVI value decreased from 0.84 to 0.58, indicating mangrove damage. However, it increased to 0.83 in May 2021, indicating rapid mangrove recovery. Additionally, the total mangrove cover gained three years after Typhoon Vongfong (August 2020 to August 2023) was approximately 47.16 hectares, or 140.19%. A total of 498 trees from nine true mangrove species were recorded in the study area, and based on the diversity analysis, the mangrove forest has low species diversity. Results also showed that the mangrove forest has a mean aboveground biomass of 199.56 plus or minus 17.42 Mg ha raised to negative one and a carbon stock estimate of 93.79 plus or minus 8.19 Mg C ha raised to negative 1 equivalent to 344.21 plus or minus 30.04 MG CO2 ha raised to negative 1. This study not only highlights the relevance of using remote sensing methods to map and determine mangrove damages and early recovery based on satellite data, but also underscores the resilience of the mangrove forest and its ability to sequester large amounts of carbon dioxide even after being devastated by a strong typhoon.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.